2019
DOI: 10.3389/fneur.2019.00232
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral-Central Neuroimmune Crosstalk in Parkinson's Disease: What Do Patients and Animal Models Tell Us?

Abstract: The brain is no longer considered an immune privileged organ and neuroinflammation has long been associated with Parkinson's disease. Accumulating evidence demonstrates that innate and adaptive responses take place in the CNS. The extent to which peripheral immune alterations impacts on the CNS, or vice and versa, is, however, still a matter of debate. Gaining a better knowledge of the molecular and cellular immune dysfunctions present in these two compartments and clarifying their mutual interactions is a fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 251 publications
5
44
0
1
Order By: Relevance
“…Indeed IL-1β enhanced pain transduction and conduction via modulation of ion channels such as TRP ankyrin 1 (TRPA1), TRPV1, and Nav1.7. CCL2 also contributes to macrophage recruitment (104,149). Thus, these factors serve to perpetuate a feedback loop between neuronal sensitization and cytokine production during tissue injury or inflammation.…”
Section: Peripheral Nociceptor Terminalmentioning
confidence: 99%
“…Indeed IL-1β enhanced pain transduction and conduction via modulation of ion channels such as TRP ankyrin 1 (TRPA1), TRPV1, and Nav1.7. CCL2 also contributes to macrophage recruitment (104,149). Thus, these factors serve to perpetuate a feedback loop between neuronal sensitization and cytokine production during tissue injury or inflammation.…”
Section: Peripheral Nociceptor Terminalmentioning
confidence: 99%
“…Neuroinflammation-mostly expressed as microglia activation-is clearly implicated in PD progression and accompanies dopaminergic cell death since the very early phase of the disease (Fuzzati-Armentero et al, 2019). GCase defects may substantially contribute to this phenomenon.…”
Section: Glucocerebrosidase and Neuroinflammationmentioning
confidence: 99%
“…Currently, there are symptom-relieving medications but no cure for the disease. The pathophysiological mechanisms are not completely known but it has been suggested that inflammation, oxidative stress, and other neurotoxic processes are involved [ 2 , 3 , 4 , 5 , 6 , 7 ]. Therefore, identification of modifiable risk factors, such as diet, that affect the risk of PD is of great importance.…”
Section: Introductionmentioning
confidence: 99%